Een mediator leest Jakobus 4:1-12: Over de samenhang van Jakobus 4:1-12 en pastorale lessen voor conflict en polarisatie - Post, S. D. (Theologia reformata, 2025)
This article employs the logic of conflict resolution to address the views that James 4,1-12 is a disjointed passage that lacks an unambiguous theme. The insights gained from this reading through the lens of a conflict mediator are then correlated to biblical-theological literature on peacemaking. The conclusions drawn provide pastors with eight recommendations for managing conflicts or increasing polarization within their congregations.